Trapped river otters (Lontra canadensis) from central Saskatchewan differ in total and organic mercury concentrations by sex and geographic location - Steven C. Wilkie; Richard H.M. Espie; Niladri Basu; Karsten Liber; Britt D. Hall (Canadian Science Publishing, 2018)
Mercury (Hg) in wildlife remains of great concern, especially for apex piscivores. Despite this, exposure information from many species in many areas is lacking, so that management decisions are hampered. Here we examine Hg concentrations in fur, liver, and kidney tissues from river otters (Lontra canadensis (Schreber, 1777)) (n = 203) to quantify existing Hg concentrations over a broad geographic area in Saskatchewan. Mean fur total Hg (THg) (9.68 ± 7.52 mg/kg fresh weight (f.w.)) was significantly correlated with THg and organic Hg (OHg) in liver and kidney tissue, showcasing the potential for using fur as a noninvasive method of monitoring Hg in top-level mammals. Livers of males had higher mean OHg concentrations than livers of females (males: 2.71 mg/kg d.w., females: 1.87 mg/kg d.w.), but not significantly so. No sex-related differences were observed in kidney OHg concentrations. THg concentrations in otter fur collected in the Boreal Shield ecozone (Churchill River Upland) were significantly higher (mean = 16.1 mg/kg f.w.) than in otter fur collected from the Boreal Plain ecozone (mean = 8.59 mg/kg f.w.). Fur from otters (n = 20; trapping block N66) trapped near a decommissioned smelter contained the highest concentrations of THg in the study (mean = 18.4 mg/kg f.w.).